A systematic review on available technologies and selection for prosthetic arm restoration. - Pawar, Bhavesh; Mungla, Mitesh (Technology & Disability, 2022)
BACKGROUND: The design, provision, and assessment of prosthetic arm technologies and related services are all dependent on an understanding of how prosthetic arms are used in everyday life. This research examines the scientific literature on prosthetic arm technologies and approaches that have been used to evaluate upper limb prosthetic arms in daily life use. OBJECTIVE: The purpose of this review paper is to give an outline of current literature, which covers the selection, design, and choices of prosthetic arm technologies. METHODS: A structural search for the available technologies on the prosthetic arm was carried out. A research database search was carried out in PubMed, Web of Science, Scopus, Crossref, Google Scholar, and questionnaires were evaluated based on available prosthetic arm technologies, material, methodology, comfortability. RESULTS: From the proposed review, it is concluded that not all prosthetic technologies suit the patients because of the difference in injuries. Every prosthetic arm technology has its advantages and limitations depending on end-user requirements and comfortability. Based on the available literature, it is observed that amputees have been given equal importance to comfortability along with functionality. Consequently, amputees may opt for a prosthetic arm technology that is easy to use and comfortable rather than an advanced technology-based prosthetic arm but less with comfortability. CONCLUSION: An attempt has been made for extensive reviews for the various types of prosthetic systems, materials, usability, methodologies, comfortability, etc. Comparative studies on various types of available prosthetic arm technologies have been also carried out with pros and cons. More specifically, the proposed paper provides a significant review of the upper limb prosthetic arm's current developments and their impacts.